(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Chat bots are the system or you can say a software that act as a normal person to solve your problems or deal with the situations that you are facing off. So, we are making a project on the bank chat bot. Which will help the users of the bank for doing any tramp. It helps like a real person such as we go to a bank for any help and we contact a person for this. But this bank chat bot will help us instead of a person to solve our worry .So, by remaining in our homes only we can get benefitted. It is a very handy software in nowadays online systems. Due to the COVID-19 people cannot get out so, people can use this initiative to solve their problems that they are facing with their banks. Our chat bot system can do every type of work that a bank can do such withdraw , deposit, knowing about the bank and each item . So it is a most beneficiary thing in our lifestyle.